Molybdenum complexes as precursors of tribologically active substances under extreme pressure conditions - Rastogi R.B.; Yadav M. (My University, 2025)
Some molybdenum complexes of N-isonicotinyl-N′ aryl thiosemicarbazides were studied for their tribological activity using four ball test machine. All the compounds were found to be significantly effective extreme pressure lubrication additives. Their EPL efficiency has been compared on the basis of various tribological parameters like wear scar diameter, friction coefficient, initial seizure load (ISL), 2.5s seizure delay load (2.5 s SDL), weld load (WL), mean Hertz load (MHL), pressure wear index (PWI) and flash temperature parameter (FTP). The topography of the wear scar surface of balls in presence of p-chlorophenyl derivative has been studied by scanning electron microscopy at 2.5s seizure delay load and just before weld load. Auger electron spectroscopy has been used to analyze the wear scar surface at just before weld load.